Changes in cigarette smoking behavior among breast cancer and unaffected women - a prospective study in the MARIE cohort - Gali, Kathleen; Bokemeyer, Frederike; Behrens, Sabine; Möhl, Annika; Obi, Nadia; Becher, Heiko; Chang-Claude, Jenny (Cancer epidemiology, 2022)
Background - Smoking cessation after a cancer diagnosis can reduce adverse cancer treatment outcomes. Whether a breast cancer diagnosis, a cancer commonly seen as unrelated to smoking cigarettes, motivates changes in smoking behavior is not fully understood. We aimed to compare long-term changes at three follow-up times of cigarette smoking behavior in women with breast cancer and baseline age- and region-matched unaffected women. - Methods - We used longitudinal data from the population-based case-control study MARIE (Mamma Carcinoma Risk Factor Investigation). Women with breast cancer (N = 3813) and unaffected women (N = 7341) aged 50-74 years were recruited from 2002 to 2005. Analyses on changes in smoking were based on data from those who also completed follow-up 1 in 2009-2012, follow-up 2 in 2014-2016 and follow-up 3 in 2020. Multinomial logistic regression for changes (quitting, stable, or start smoking) adjusted for age, study region, education, comorbidities, living situation, and follow-up time, was applied to examine the associations between breast cancer status and changes in smoking behavior. - Results - Women with breast cancer had significantly higher odds than unaffected women of quitting smoking (OR = 1.38, 95 % CI: 1.01-1.89) and lower odds of returning to smoking (OR = 0.29, 95 % CI: 0.09-0.94) at follow-up 1, but were more likely to start or return to smoking at follow-up 2 (OR = 2.11, 95 % CI 1.08-4.15). No significant group differences were found for changes in smoking behavior at follow-up 3. - Conclusion - Our findings indicate that short-term changes in smoking behavior can be attributed to a breast cancer diagnosis, but that over time the effect diminishes and changes in smoking no longer differ between breast cancer and breast cancer-free women. To support smoking cessation and to prevent relapse, guidelines to address smoking in cancer care, as well as comprehensive tobacco treatment services, are needed.
Gesehen am 30.01.2023